Performance evaluation of Dabasso Lamaffaa Small Scale Irrigation Scheme at Buno Bedele Zone, South West Ethiopia - Ashine, Etefa Tilahun; Mengesha, Addisu Assefa; Bedane, Minda Tadesse; Kebede, Hewan Tadesse (Frontiers in Agronomy, 2025)
Evaluating the performance of irrigation schemes is crucial to identify key problems that impede scheme efficiencies and the utilization of available resources. Accordingly, the objective of this study was to evaluate the performance of Dabasso Lamaffa small-scale irrigation scheme. The study was carried out during the cropping season from November up to March 2015 E.C. Primary and secondary data were collected for implementing the efficiency and productivity of the scheme. To collect and measure the relevant data at the field level, the three representative farmers’ fields were selected at the head, middle, and tail-end water users in the irrigation scheme. Both internal and external performance indicators were considered for evaluation of the scheme. The internal indicators were conveyance efficiency, application efficiency, storage efficiency, distribution uniformity, and deep percolation ratio. The external indicators were agricultural output, water supply indicators, water delivery capacity indicators, physical indicators, and economic and financial indicators. The result reveals that the average efficiency of conveyance, application, storage, deep percolation ratio, and the distribution uniformity of the scheme were 76.44%, 30.47%, 82.74%, 69.53%, and 95.29%, respectively. The overall efficiency of the scheme was 23.29%, showing that the performance was poor, and it was caused mainly due to the water application problem at the field. The agricultural output productivity was 2620.83 (US$/ha), 2501.71 (US$/ha), 0.94 (US$/m3), and 0.91 (US$/m3), respectively, for output per unit irrigated area, output per unit command area, output per unit irrigation diverted, and output per unit water consumed. This result reveals that it was in a recommended output production, and in these regards the scheme was productive. The water supply indicators, such as relative irrigation supply (RIS) and relative water supply (RWS), were 2.13 and 2.05, which shows that there was no deficiency of water and it was supplied in excess. However, the water delivery capacity of the scheme was low, which was 83%, and it needs improvement. The irrigation ratio and the sustainability of the irrigation scheme were also good, showing there will be a continuation of using the scheme in the future. Awareness creation for the farmers on the field water management is essential to improve the economic and financial benefit of the scheme in the future.